Electromagnetic field correlations and sound waves - Sokolovsky, A.I.; Stupka, A.A. (Вопросы атомной науки и техники, 2007)
Statistical operator of the many component plasma has been found on the basis of the Bogolyubov reduced description method and quasi-relativistic quantum electrodynamics. Calculations were carried out in the Hamilton gauge up to the second order of a perturbation theory in interaction. Closed system of equations for binary correlations of electromagnetic field and hydrodynamic variables of medium has been obtained and investigated near equilibrium. Classical Maxwell plasma approximation was studied. Coupled states of sound waves and waves of transversal correlation of the field were predicted. Waves of correlations of electromagnetic field can be excited by sound waves in plasma. Статистичний оператор багатокомпонентної плазми знайдено на основі метода скороченого опису Боголюбова та квазірелятивістської квантової електродинаміки. Обчислення проведено у калібровці Гамільтона з точністю до другого порядку теорії збурень за взаємодією. Одержано замкнену систему рівнянь для бінарних кореляцій поля та гідродинамічних змінних середовища і досліджено біля рівноваги. Вивчено наближення класичної максвеллівської плазми. Передбачено зв’язані стани звукових хвиль та хвиль поперечних кореляцій поля. Хвилі кореляцій електромагнітного поля можуть бути збуджені звуковими хвилями у плазмі. Статистический оператор многокомпонентной плазмы найден на основе метода сокращенного описания Боголюбова и квазирелятивистской квантовой электродинамики. Вычисления проведены в калибровке Гамильтона с точностью до второго порядка теории возмущений по взаимодействию. Получена замкнутая система уравнений для бинарных корреляций электромагнитного поля и гидродинамических переменных среды и исследована около равновесия. Изучено приближение классической максвелловской плазмы. Предсказаны связанные состояния звуковых волн и волн поперечных корреляций поля. Волны корреляций электромагнитного поля могут быть возбуждены звуковыми волнами в плазме.